The impact of free cash flow on firm’s performance: evidence from Malaysia - Kok, Elaine Suit Lai; Abdul Latiff, Ahmed Razman; Ooi, Chee Keong; Tong, Chue Qun (Springer Cham, 2020)
The objective of this chapter is to investigate the impact of free cash flow (FCF) on a firm’s performance. This research is using the data from 2013 to 2017 from Malaysia and various industries as the moderating variable. Whereas, firm performance is measured by operating performance, firm value, and stock return as the dependent variables. All the explanatory variables are tested as whether they have any significant relationship on the firm’s performance as the dependent variables. The firm performance is measured by the company’s accounting performance, which measured by return on asset (ROA) and return on equity (ROE), firm value is measured by Tobin’s Q and the stock return measure by stock price. The data collected are categorized into five different industries, which include finance, plantation, industrial products, properties, and consumer goods. This chapter utilizes panel data regression for testing the hypothesis and the results indicated that some do not support the hypothesis. The findings point out that FCF as the independent variables has a significantly negative relationship with the firm’s performance, measured by ROA and Tobin Q. Besides that, there is a positively insignificant relationship between ROE and stock return on FCF.